2019
DOI: 10.1080/11038128.2019.1622771
|View full text |Cite
|
Sign up to set email alerts
|

Perceived occupational balance and well-being among people with mental illness living in two types of supported housing

Abstract: Background: People with psychiatric disabilities often struggle with maintaining a satisfying occupational balance. Knowledge about factors of relevance for occupational balance in this group is therefore vital for improving their support. Aim: The aim was to describe perceptions of occupational balance among people with psychiatric disabilities living in supported housing (SH) or in own flat/house with housing support (OHS). Potential importance of housing context and socio-demographic, well-being and recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In our study, we detected no gender differences in OB. However, previous studies reported gender-based differences in OB in mental illness and rheumatoid arthritis, with females reporting lower OB than males (Eklund, Brunt and Argentzell, 2020;Wagman, et al, 2020). However, other researchers determined that males had lower OB than females in a general population (Wagman et al, 2014).…”
Section: Discussionmentioning
confidence: 92%
“…In our study, we detected no gender differences in OB. However, previous studies reported gender-based differences in OB in mental illness and rheumatoid arthritis, with females reporting lower OB than males (Eklund, Brunt and Argentzell, 2020;Wagman, et al, 2020). However, other researchers determined that males had lower OB than females in a general population (Wagman et al, 2014).…”
Section: Discussionmentioning
confidence: 92%